2018
DOI: 10.7150/jca.22755
|View full text |Cite
|
Sign up to set email alerts
|

The value of preoperative Glasgow Prognostic Score and the C-Reactive Protein to Albumin Ratio as prognostic factors for long-term survival in pathological T1N0 esophageal squamous cell carcinoma

Abstract: Plenty of studies have confirmed the prognostic values of inflammation-based prognostic scores in many malignant tumors. In present study, we aim to explore whether these indexes has same prognostic values in patients with stage T1N0 esophageal squamous cell carcinoma (ESCC). The clinicopathological data of 160 consecutive patients with pathological stage T1N0 ESCC from January 2005 to December 2012 were collected retrospectively. As prognostic factors, the inflammation-based prognostic scores, including C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 42 publications
(49 reference statements)
0
53
0
Order By: Relevance
“…Recently, Yu et al . explored the prognostic value of inflammation‐based prognostic scores, including the CRP, NLR, PLR, GPS, prognostic index, and CRP/Alb ratio in T1N0 esophageal squamous cell carcinoma and found that only GPS and CRP/Alb ratio were predictive of long‐term survival in multivariate analyses . In summary, most previous reports suggest that the prognostic ability of the CRP/Alb ratio could be comparable with that of GPS and superior to that of other inflammation‐based prognostic scores.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Recently, Yu et al . explored the prognostic value of inflammation‐based prognostic scores, including the CRP, NLR, PLR, GPS, prognostic index, and CRP/Alb ratio in T1N0 esophageal squamous cell carcinoma and found that only GPS and CRP/Alb ratio were predictive of long‐term survival in multivariate analyses . In summary, most previous reports suggest that the prognostic ability of the CRP/Alb ratio could be comparable with that of GPS and superior to that of other inflammation‐based prognostic scores.…”
Section: Discussionmentioning
confidence: 90%
“…These biomarkers can be evaluated easily by sampling a small amount of peripheral blood. Prognostic significance has been gradually elucidated by accumulation of data from studies in gastrointestinal tumors such as esophageal cancer, gastric cancer, and colorectal cancer . However, few studies about the relationship between these biomarkers with respect to prognosis in patients with AEG have been published.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations